`f(x) = (1 - x e^x)/(x + e^x)` Differentiate.

Textbook Question

Chapter 3, 3.2 - Problem 24 - Calculus: Early Transcendentals (7th Edition, James Stewart).
See all solutions for this textbook.

1 Answer | Add Yours

balajia's profile pic

balajia | College Teacher | (Level 1) eNoter

Posted on

`f'(x)=(-(x+e^x)(e^x+xe^x)-(1-xe^x)(1+e^x))/(x+e^x)^2`

`f'(x)=((xe^x-1)(1+e^x)-(x+e^x)(1+x)e^x)/(x+e^x)^2`

`f'(x)=-(x^2e^x+e^(2x)+e^x+1)/(x+e^x)^2`

``

We’ve answered 318,917 questions. We can answer yours, too.

Ask a question